Cohesion in The Abstract of The Theses Written by Undergraduate Students of English Education Program - Dania, Rahma (Universitas PGRI Sumatera Barat, 2018)
This study aims to explore the realization of cohesive devices in the abstracts of the theses written by undergraduate students of English Education Program at a state university in Bandung. This study also attempts to reveal the contributions of the cohesive devices used by the students in their abstract to build the cohesiveness of the text. This study belongs to a descriptive study involving 42 abstracts as the data of the study. This study exposes two main findings. First, cohesive devices that are employed in students’ abstract are reference, conjunction, substitution, and lexical cohesion. Second, each device gives significant contribution to the cohesiveness of students’ abstract. Reference contributes to keep track of the participants of the text and help readers to point to something within or outside the text. Lexical cohesion also contributes to keep tract of the participants of the text. Meanwhile, the contribution of conjunction in students’ abstract is to connect the preceding part with the next one systematically. In addition, substitution is used by the students to avoid repetition in their abstract. Based on these findings, it can be concluded that cohesive devices are important devices to create cohesive abstracts.